2007
DOI: 10.1038/cr.2007.53
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of primary neuroepithelial progenitor and brain endothelial cells: distinct effect on neural progenitor maintenance and differentiation by soluble factors and direct contact

Abstract: Neurovascular interactions are crucial for the normal development of the central nervous system. To study such interactions in primary cultures, we developed a procedure to simultaneously isolate neural progenitor and endothelial cell fractions from embryonic mouse brains. Depending on the culture conditions endothelial cells were found to favor maintenance of the neuroprogenitor phenotype through the production of soluble factors, or to promote neuronal differentiation of neural progenitors through direct con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…In the past, brain endothelial cells have shown to interact with neural stem cells from the central nervous system (CNS) in different ways. In 2007, Sosa et al (2004) showed that depending on the co-culture system, endothelial cells either promote self-renewal of neural stem cells via soluble factors as originally described by Shen et al (2004) or promote neuronal differentiation by direct contact (Shen et al 2004;Gama Sosa et al 2007). To the best of our knowledge, this is the first study where the direct interaction of primary murine ENSc and MVCs was investigated.…”
Section: Figmentioning
confidence: 88%
“…In the past, brain endothelial cells have shown to interact with neural stem cells from the central nervous system (CNS) in different ways. In 2007, Sosa et al (2004) showed that depending on the co-culture system, endothelial cells either promote self-renewal of neural stem cells via soluble factors as originally described by Shen et al (2004) or promote neuronal differentiation by direct contact (Shen et al 2004;Gama Sosa et al 2007). To the best of our knowledge, this is the first study where the direct interaction of primary murine ENSc and MVCs was investigated.…”
Section: Figmentioning
confidence: 88%
“…Primary neuronal cultures were prepared from the cerebral cortex isolated from E15.5-16 embryos as previously described [86,87] and maintained in Neurobasal medium/B27 supplement (Invitrogen) for 5-7 days in vitro (DIV). For treatment with insulin or IGF-1, neurons were maintained overnight in neurobasal medium devoid of B27 supplement and then treated as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Using cocultures, we found that proliferation and Sox2 expression are increased in SVZ cells in contact with BEC. However, these effects may also be due to diffusible soluble factors, based on the fact that NSCs derived from embryonic and postnatal rodents remain undifferentiated, and proliferate in the presence of EC-derived diffusible cues (Shen et al, 2004; Gama Sosa et al, 2007; Plane et al, 2010; Sun et al, 2010). Therefore, we also determined the proportion of Sox2+ cells and BrdU+ cells in SVZ cells that were not in contact with BEC, but were exposed to EC diffusible factors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, direct coculture of mouse or human embryonic NSCs with EC increased neuronal differentiation (Mathieu et al, 2006; Gama Sosa et al, 2007; Chintawar et al, 2009). Although there are differences in the developmental status of the cells used in these studies as compared to our cells, the timing of the cocultures may be critical in explaining the apparent discrepancies: indeed we examined neuronal differentiation and commitment at 24 h due to the viability of BEC, while the other studies used later time points (up to 8 days).…”
Section: Discussionmentioning
confidence: 99%